„Nie budujcie mi pomników”. Wizja Świętego Jana Pawła II w sztuce sakralnej - Steliga, Anna (Dydaktyka Polonistyczna, 2016)
In Poland there is a cult of saint John Paul II. Presentations of his figure occur in any field of art(eg. in painting, sculpture, stained glass, mosaics, etc.). Most of those works are copies of imagesof the pope. Low price of work and realism in portraits – that’s what recipients wants. The worldof modern art also tries to show the figure of John Paul II. Artists pay attention mainly to the socialphenomenon, occurrence of pop culture, which a figure of the pope has become. This aroused andis still arousing controversy among the faithful. The article presents selected examples of successfuland less successful artists’s approach to this topic